Pattern of Precipitating Causes of Diabetic Ketoacidosis in A Tertiary Care Hospital of Bangladesh - Rahim, Muhammad Abdur; Rouf, Rozana; Ahmed, Ashraf Uddin; Uddin, Khwaja Nazim; Latif, Zafar Ahmed (Bangladesh Journal of Medicine, 2018)
Background: Diabetic ketoacidosis (DKA) is an established presenting feature of type 1 diabetes mellitus, but infection and non-compliance to anti-diabetic treatment remain the major precipitating causes of DKA among diagnosed diabetic patients. This study was designed to evaluate the precipitating causes of DKA occurring among adult patients. Methods: This cross-sectional study was done in Bangladesh Institute of Research and Rehabilitation in Diabetes, Endocrine and Metabolic Disorders (BIRDEM) General Hospital, Dhaka, Bangladesh from 2008 to 2011. Diagnosed adult DKA cases were consecutively and purposively included in this study. Patients were evaluated clinically and by laboratory tests aiming at identification of precipitating causes along with management. Results: Total patients were 200 with slight female (56%) predominance. Mean age of the study subjects was 37.6±7.5 years. Incidence of DKA was more in known diabetic patients (71%), more among rural population (53%) and low income group (76.5%). Infection (45.5%) was the commonest precipitating cause followed by non-adherence to anti-diabetic therapy (31%). Acute pancreatitis (5%), acute myocardial infarction (2%), stroke (1%) and surgery (1.5%) were less common causes and etiology could not be identified in 14% cases. Severe acidosis (pH < 7) was less common (8.5%). Neutrophil leukocytosis was present in 87% cases. Mortality was 6.5%. Conclusion: Over two-thirds of DKA cases were precipitated by infection and non-compliance to anti-diabetic treatment in this study. In a significant number of cases, no cause could be identified. Acute pancreatitis appeared as an important cause of DKA in this study. Bangladesh J Medicine Jan 2018; 29(1) : 3-6